Knowledge and practice of the ideal birth interval amongst parturients attending primary health centre Aluu, Rivers State, Nigeria - Kasso, Terhemen; Ezebuiro, Emmanuella Ijeoma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Birth interval is a period for the mother to heal completely from the events of pregnancy. Short birth interval (<24 months) is associated with grave consequences on maternal and child health and the impact is more on families with poor socioeconomic status. Aim was to assess the knowledge and practice of ideal birth interval amongst parturients at primary health centre- Aluu. Methods: This was a descriptive cross-sectional study to assess the knowledge and practice of ideal birth interval and its health benefits among parturients attending primary health centre, Aluu in September, 2021. The data was collected using structured self-administered questionnaires, analysed with SPSS version 23.0 and presented in tables and charts. Results: Knowledge of ideal birth interval among the respondents was 68.3%. Regarding its benefits, 34.2% of the respondents knew that it replenishes lost nutrients, 20.2% knew it prevents anaemia, 24.7% knew it improves pregnancy outcome while 67.7% knew that it helps in financial planning. Only 42.86% of the respondents practised ideal birth interval, 47.6% had discussed it with their health worker and 89.1% said it should be included in the routine antenatal teachings. Many (41.8%) of the respondents did not use any form of contraception. Conclusions: There was poor knowledge of the health benefits of ideal birth interval and less than half of the respondents practiced ideal birth interval and contraceptive use. Therefore, there is need for more education by health care workers on ideal birth interval and its benefits and the use of modern contraceptive methods during routine antenatal teachings.